An a Priori Analysis of Validity Evidence on The Speaking Section of TPELT, a Developed English Proficiency Test for Primary English Teachers - Agus Syahiddin; Ika Lestari Damayanti; Della N. Kartika Sari (English Department - University of Sultan Ageng Tirtayasa, 2023)
This article introduces a new English proficiency test, TPELT (The Test for Primary English Language Teachers), which has been developed for primary English teachers in non-native English speaking countries, with a focus on Indonesia. The study examines the a priori validity analysis of TPELT's speaking test, with the goal of demonstrating its usefulness in assessing English proficiency. The article also discusses the concept of validity and its significance in test development, as well as the two methods for establishing validity. The researchers used a descriptive qualitative approach to gather and analyze data for the study, including documents, checklists, and interviews with the TPELT developers. To assess the a priori validity of the test, the researchers employed Wier's framework and analyzed TPELT's blueprint alongside frameworks for each English skill assessed in the test. The a priori validity analysis findings indicate that TPELT is a valid test for measuring English proficiency and competence among teachers. The evidence supports the test's theory-based and context validity, and its convenience and comprehensiveness make it an ideal choice for assessment purposes.